The effect of BCG vaccination on alveolar macrophages obtained from induced sputum from healthy volunteers. (September 2020) - Koeken, Valerie A.C.M.; van der Pasch, Eva S.; Leijte, Guus P.; Mourits, Vera P.; de Bree, L. Charlotte J.; Moorlag, Simone J.C.F.M.; Budnick, Isadore; Idh, Nina; Lerm, Maria; Kox, Matthijs; van Laarhoven, Arjan; Netea, Mihai G.; et al.
Highlights: Viable alveolar macrophages can be collected from induced sputum. Smoking increases the expression of activation markers on alveolar macrophages. BCG vaccination decreases CD11b and HLA-DR expression on alveolar macrophages. Abstract: The anti-tuberculosis vaccine Bacillus Calmette-Guérin (BCG) is able to boost innate immune responses through a process called 'trained immunity'. It is hypothesized that BCG-induced trained immunity contributes to protection against Mycobacterium tuberculosis infection. Since alveolar macrophages are the first cell type to encounter M. tuberculosis upon infection, we aimed to investigate the immunomodulatory effects of BCG vaccination on alveolar macrophages. Searching for a less-invasive method than bronchoalveolar lavage, we optimized the isolation of alveolar macrophages from induced sputum of healthy volunteers. Viable alveolar macrophages could be successfully isolated from induced sputum and showed signs of activation already upon retrieval. Further flow cytometric analyses revealed that at baseline, higher expression levels of activation markers were observed on the alveolar macrophages of smokers compared to non-smokers. In addition, BCG vaccination resulted in decreased expression of the activation markers CD11b and HLA-DR on alveolar macrophages. Future studies should evaluate the functional consequences of this reduced activation of alveolar macrophages after BCG vaccination.